The Effect Of Counter Pressure And Kneading Techniques On Reducing The Intensity Of Labor Pain In The First Stage Of Active Phase - Evi Sriayuningtyas; Resi Galaupa (International Journal of Health and Pharmaceutical (IJHP), 2022)
Pain is a form of discomfort felt by the mother at the time of delivery. One way that can be used to overcome the problem of pain during labor is to apply massage techniques. Among them, the counter pressure massage technique can be done in the lumbar region using the heel of the hand or fist. And the kneading technique is massaging or squeezing using the palms of the hands or fingers to pinch some parts of the skin. The purpose of this study was to determine the effect of counter pressure and kneading techniques on reducing pain intensity in the first stage of normal delivery in primiparous mothers at BPM Evi Sriaayuningtyas. Method This type of research is a Quasi Experiment with a one-group pretest-posttest design approach. The population in this study were all mothers who gave birth vaginally at BPM Evi Sriaayuningtyas in March-April 2022, a sample of 30 people was obtained using purposive sampling technique. Research Results: Based on the results of hypothesis testing using the Wilcoxon test, the value of < (0.000 < 0.05) stated that there was an effect of counter pressure techniques and kneading techniques on reducing pain intensity in the first stage. Conclusion The application of counter pressure techniques and kneading techniques can be used as a intervention in helping mothers in labor to cope with labor pain.